Memórias da Vila "A": lazer e sociabilidade de trabalhadores de Itaipu - Lima, Sancléya Evanessa de (2019)
As far as leisure activities are concerned, Binational Itaipu allows the study of various representations. This company´s organization offered a background for distinct interpretations, by creating three housing complexes for the employees, as well as leisure and conviviality environments, in the company itself and in other spaces it created. This paper´s goal is to understand what was caused in the life of those workers who came to build Itaipu plant and live at Vila “A”, during the 1970 and 1980 decades, in terms of leisure practices and sociability. Within this objective, qualitative research had the purpose of searching data in official documents, pictures, UNICON magazines, in the debate with authors and in memories. These memories were also analyzed by means of 13 interviews (oral history), of which 12 were “Vila “A”” residents, who had employment relationship with Itaipu in the initial years of its construction and another interview with the architect in charge of planning and building Itaipu neighborhoods. Leisure experiences and sociability of these workers were influenced by the new working environment, living conditions, in a city which is different from the one they were used to, in a border context. Another impact was cause by the fact that they became workers of a company that was building a huge venture, unique in the country, with international acclaim. Though having its own living style, motivated by Itaipu, some habits were not erased, but adopted to a new reality, which brings a new collective identity reading of Itaipu workers in the 1970´s and 1980´s.